Effects of media components on arachidonic acid production by Candida krusei under submerged condition - Laing, Penelope Ering (2013)
Arachidonic acid (ARA) is a long chain polyunsaturated fatty acid (PuFA) of the omega-6 class (5,8,11,14-eico-satetraenoic acid). It plays an important role in the structure and function of biological membranes (Yu et al., 2002), which also as an essential fatty acid in human nutrition and a biogenetic precursor. The aim of this study is to develop an optimum media component (glucose, potassium nitrate (KNO3), potassium phosphate monobasic (KH2PO4), and glutamate) to yield the highest production of ARA by Candida krusei under submerged condition. The media components are studied at different levels which are from 10 to 80 g/L for glucose, 1 to 5 g/L for KNO3, 1 to 5 g/L for KH2PO4 and 0 to 0.8 g/L for glutamatewhich are determined using Design Expert. The total ARA composition will be determined by gas chromatography (GC) with capillary column 0.25 mm x 30 m x 0.25 µm, using helium as the carrier gas and at initial column temperature at 185 °C which then will increase at a rate of 3.5 °C min-1 to 235 °C.From this study, the expected optimum conditions that will be achieved is with glucose concentration, 10.0 g/L, KH2PO4 concentration, 1.0 g/L, KNO3 concentration 1.0 g/L and concentration of glutamic acid, 0.8 g/L which resulted in maximum production of ARA(1.39 g/L). In a conclusion, the optimization of media to produce high amount of ARA using microorganism is a suitable alternative way to produce ARA which benefits everyone besides getting ARA from porcine liver which is prohibited in certain community such as the Muslims and vegetarians.